PENGARUH DISIPLIN, MOTIVASI DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN AREA LAYANAN MIKRO DI PT. BANK JATENG CABANG PEMALANG - Muhwan Muhwan; Siti Puryandani (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
The purpose of this study was to determine and analyze the influence of Discipline, Motivation and Work Experience on the Work Productivity of Micro Service Area Employees at PT Bank Jateng Pemalang Branch. The research method uses a sample of 36 employees using the census method, while the analysis used is a quantitative descriptive method with multiple correlations and multiple regression approaches. Based on the results of the equation analysis, the regression obtained is as follows: Y = 17,961 + 3,241X1 + 1,476X2 + 0,988X3, where X1 = Work Discipline, X2 = Work Motivation, and X3 = Work Experience. Based on hypothesis testing using the T test that motivation and work experience have a positive and significant effect on employee productivity. The results of the study simultaneously using the F test, showed that all independent variables significantly influence employee productivity. R Square value of 0.289. This means that the contribution of the influence of discipline, motivation and experience on productivity is 28.9% while the remaining 71.1% is influenced by other variables not included in this study.